Preparation and Evaluation of Carbamazepine Particles Loaded in Mucoadhesive Film for Treatment of Trigeminal Neuralgia - Fatemeh Ahmadi; Mohammad Reza Mazloomi; Elahehnaz Parhizkar (Shiraz University of Medical Sciences, 2024)
The trigeminal nerve is the largest craniofacial nerve, responsible for detecting sensory stimuli originating from the cranial and facial areas. Trigeminal neuralgia is a common form of craniofacial neuropathic pain that causes one of the most severe pain episodes a person can endure. The pain attacks would impact quality of life and mental health of patients. Carbamazepine and oxcarbazepine are recommended as first-line treatments to control pain in patients with trigeminal neuralgia. Oral administration of the mentioned drugs requires higher doses and as a result, higher risk of side effects due to the metabolic processes. Local mucosal drug delivery might be a proper alternative for oral systemic therapy in order to localize the treatment and reduce the side effects. The goal of this study was to develop an oral film containing particles of carbamazepine for treatment of trigeminal neuralgia. Particles were prepared by solvent evaporation method using chloroform and dichloromethane as organic solvents and ethyl cellulose and hydroxypropyl methylcellulose as coating polymers. The optimized particle contained equal weight ratios of polymers and was prepared using chloroform. The particles released about 70% of carbamazepine content within an hour. Optimized particles were loaded in an oral film containing 5% acacia, 10% gelatin as the film-forming polymers, and 1% glycerol and 10% PEG 400 as plasticizers. Satisfactory results were obtained from evaluation of physical characteristics of carbamazepine loaded film including: peak load was equal to 1506 mN, average thickness was 0.49 ± 0.003 mm and average weight was 1.53 ± 0.005 g. Film was completely dissolved in water. Also, release of the pure and coated drug from the optimized film was about 55% and 30%, respectively within 1 hour and about 42% and 80%, respectively after 2 hours. These preliminary results indicate that polymeric film containing particles can be a potentially successful system for delivery of carbamazepine to the oral mucosa.